Public Perception and Effectiveness of Punishment for Khalwat Perpetrators in Aceh - Bastiar Bastiar; Asmuni Asmuni; Bukhari Bukhari (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
This study examines the public's perception of khalwat and the effectiveness of punishment against perpetrators’ violation of khalwat in Aceh. This study is a normative-empirical study with qualitative data. Data sources are the Constitution of 1945, Law No. 1 of 1946 on the Criminal Code, Law No. 8 of 1981 on the Criminal Procedure Code, and Qanun Aceh No. 6 of 2014 on the Jinayat Law. Field data are sourced from the community, leaders, religious leaders, academics, the Syar'iyah Court, and khalwat perpetrators. The results showed that generally, the community supports the establishment of the rule of jinayat khalwat for the sake of benefit. The establishment of Qanun Jinayat reflects the Islamic life of the Acehnese people so that the protection of self-respect and their families is inseparable. The application of penalties for khalwat violations has not been effective in all regions of Aceh province. However, some areas implement the punishment effectively, proven by the decrease in cases of khalwat violations. However, the application of punishment to khalwat perpetrators did not positively affect other parts of the region””the number of jinayat khalwat that occurred increased. Therefore, punishment for khalwat perpetrators must be able to change the perpetrator’s behavior and become a lesson for the general public. Moreover, the government is advised to be more aggressive in socializing this Qanun. This research provides information and input for the government, law enforcement, and the community in Aceh.Penelitian ini mengkaji persepsi masyarakat tentang khalwat dan efektivitas hukuman terhadap pelaku pelanggaran khalwat di Aceh. Kajian ini adalah kajian normatif-empiris dengan jenis data kualitatif. Data dokumen berupa peraturan perundang-undangan, Sementara data lapangan bersumber dari masyarakat, tokoh, agama, akademisi, Mahkamah Syar’iyah dan pelaku khalwat. Hasil penelitian menunjukkan; umumnya masyarakat mendukung pembentukan aturan jinayat khalwat demi kemaslahatan. Pembentukan Qanun Jinayat merupakan refleksi kehidupan masyarakat Aceh yang Islami sehingga perlindungan terhadap kehormatan diri dan keluarganya tidak dapat dipisahkan. Umumnya masyarakat mendukung pembentukan aturan jinayat khalwat demi kemaslahatan. Pembentukan Qanun Jinayat merupakan refleksi kehidupan masyarakat Aceh yang Islami sehingga perlindungan terhadap kehormatan diri dan keluarganya tidak dapat dipisahkan. Penerapan hukuman terhadap pelanggaran Khalwat belum efektif di semua daerah di provinsi Aceh, meski demikian ada sebagian wilayah yang efektif jika dilihat dari penurunan kasus. Namun, penerapan hukuman terhadap pelaku khalwat tidak memberikan efek positif di sebagian wilayah yang lain. Jumlah jinayat khalwat yang terjadi justru meningkat. Karenanya, hukuman bagi pelaku khalwat harus mampu merubah prilaku pelaku, menjadi pelajaran bagi masyarakat umum, dan pemerintah disarankan lebih gencar mensosialisasikan Qanun ini, khususnya sosialisasi terhadap pengaturan, hikmah pelarangan khalwat dan dampak buruk khalwat. Penelitian ini menjadi informasi dan masukan bagi pemerintah, penegak hukum dan masyarakat di Aceh